The Influence of Organizational Culture, Human Resource Capacity Development, and Empowerment of Human Resources on Affective Commitment and Loyalty, and Its Implications on Employee Performance (A Survey on Employees of PT. Kereta Api Indonesia (Persero), Operational Area 2 Bandung) - Ading Rahman Sukmara; Sidik Priadana; Senen Machmud; Eddy Yusuf; Azhar Affandi (International Journal of Artificial Intelligence Research, 2022)
The successful implemenstation of tasks in the transportation service of PT. Kereta Api Indonesia (Persero), Operational Area 2 Bandung, depends greatly on the quality of employees who produce high-quality performance, ultimately enhancing company performance. This research aims to understand and examine the influence of Organizational Culture, Human Resource Capacity Development, and Empowerment of Human Resources on Affective Commitment and Loyalty, and their implications for Employee Performance. This study adopts a descriptive and verificative approach, utilizing quantitative research methods with descriptive analysis and verification analysis. The sample for this research consists of 145 employees. The analysis method employed in this study is Structural Equation Model (SEM) analysis. The research findings conclude that there is a significant influence of Organizational Culture, Human Resource Capacity Development, and Empowerment of Human Resources on Affective Commitment, with an influence magnitude of 72.02 percent. Additionally, there is a significant influence of Organizational Culture, Human Resource Capacity Development, and Empowerment of Human Resources on Employee Loyalty, with an influence magnitude of 74.48 percent. Furthermore, there is a significant influence of Affective Commitment and Loyalty on Employee Performance, with an influence magnitude of 82.74 percent. Human Resource Capacity Development, and Empowerment of Human Resources on Employee Loyalty, with an influence magnitude of 74.48 percent. Furthermore, there is a significant influence of Affective Commitment and Loyalty on Employee Performance, with an influence magnitude of 82.74 percent. Human Resource Capacity Development, and Empowerment of Human Resources on Employee Loyalty, with an influence magnitude of 74.48 percent. Furthermore, there is a significant influence of Affective Commitment and Loyalty on Employee Performance, with an influence magnitude of 82.74 percent.